Agrobacterium tumefaciens-induced bacteraemia does not lead to reporter gene expression in mouse organs. - Igor V Petrunia (Public Library of Science (PLoS), 2008)
Agrobacterium tumefaciens is the main plant biotechnology gene transfer tool with host range which can be extended to non-plant eukaryotic organisms under laboratory conditions. Known medical cases of Agrobacterium species isolation from bloodstream infections necessitate the assessment of biosafety-related risks of A. tumefaciens encounters with mammalian organisms. Here, we studied the survival of A. tumefaciens in bloodstream of mice injected with bacterial cultures. Bacterial titers of 10(8) CFU were detected in the blood of the injected animals up to two weeks after intravenous injection. Agrobacteria carrying Cauliflower mosaic virus (CaMV) 35S promoter-based constructs and isolated from the injected mice retained their capacity to promote green fluorescent protein (GFP) synthesis in Nicotiana benthamiana leaves. To examine whether or not the injected agrobacteria are able to express in mouse organs, we used an intron-containing GFP (GFPi) reporter driven either by a cytomegalovirus (CMV) promoter or by a CaMV 35S promoter. Western and northern blot analyses as well as RT-PCR analysis of liver, spleen and lung of mice injected with A. tumefaciens detected neither GFP protein nor its transcripts. Thus, bacteraemia induced in mice by A. tumefaciens does not lead to detectable levels of genetic transformation of mouse organs.